Senyawa Flavor Hasil Hidrolisis dari Ikan Seluang ( Rasbora sp) sebagai Sumber MSG (Monosodium glutamate) Alami - Wulandari Wulandari; Tiara Suci Cahyani; Siti Ayu Ulfadillah; Desliana Opie Harliani (Seminar Nasional Lahan Suboptimal, 2019)
Wulandari W, Cahyani TS, Ulfadillah SA, Harliani DO. 2019. Flavor compounds of hydrolysys result from seluang fish as a source of natural MSG (Monosodium glutamate). In: Herlinda S et al. (Eds.),Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang 4-5 September 2019. pp. 496-501. Palembang: Unsri Press.Seluang is a type of fish that is widely lived in the Banyuasin of South Sumatra. Seluang contains 361 kilocalories of energy, 10 g of protein, 5.3 g of carbohydrate, 3.2 g of fat, 80 mg of calcium, 224 mg of phosphor, and 4.7 mg of iron and contains glutamate amino acids needed in making flavoring (MSG). Making of natural MSG from Seluang fish protein hydrolyzate to avoid damage to nerve cells in the body. The method used in writing this paper is to use the literature study method . The process of making natural MSG by adding a weak acids, enzymatic reactions and anaerobic fermentation process. Writing LKTI with the title of Flavor Compound of Hydrolysys Results from Seluang Fish As a Source of Natural Monosodium Glutamate (MSG) with fermentation method carried out with two time treatments, namely fermentation 21 days and 46 days. Then the solution will be obtained and the oven process is carried out to obtain natural MSG powder from Seluang.Key words: fish protein hydrolyzate, glutamate, monosodium glutamate, seluang fish